A unified approach to the study of language contact: Cross-language priming and change in adjective/noun order. (December 2021) - Adamou, Evangelia; Feltgen, Quentin; Padure, Cristian
Aims and objectives/purpose/research questions: The connection between language contact and the bilingual speaker goes back to foundational authors in the field of contact linguistics. Yet there is very little work that combines these two levels in a single study. In this paper, we propose a unified approach to language contact by testing the role of cross-language priming (CLP) on contact-induced change at the level of complex noun phrases (NPs). Design/methodology/approach: We conducted three studies with different types of data. In Study 1, we analyse the Romani Morpho-Syntax database to identify word order preferences in Romani dialects from different countries. In Study 2, we examine a corpus of interviews in Romani from Romania. In Study 3, we conduct an experiment to test short-term priming in adjective (ADJ)/noun (N) order from Romanian to Romani and within Romani. Data and analysis: In Study 1, we examine the word order in approximately 3000 NPs from 119 Romani speakers. In Study 2, we analyse a speech corpus of 9400 words from four elderly Romani–Romanian bilinguals. In Study 3, 90 Romani–Romanian bilinguals participated in a priming experiment. We used multinomial mixed-effects logistic regression, Bayesian models and Random Forests to analyse the experimental results. Findings/conclusions: Study 1 shows that Romani speakers from Romania stand out for their frequent use of postnominal ADJs. Study 2 confirms these uses in free speech. Study 3 reveals significant CLP effects, whereby speakers favour the use of determiner (DET)–N–ADJ order in Romani immediately following a noun with a suffixed determiner (NDET) –ADJ sentence read in Romanian. Originality: Our study is the first to demonstrate CLP effects in ADJ/N order. Significance/implications: We illustrate a unified approach to language contact by introducing theoretical and methodological advances from the field of bilingualism into the study of contact-induced change.